2009
DOI: 10.1007/s11630-009-0020-x
|View full text |Cite
|
Sign up to set email alerts
|

Study on forced convective heat transfer of non-newtonian nanofluids

Abstract: This paper is concerned with the forced convective heat transfer of dilute liquid suspensions of nanoparticles (nanofluids) flowing through a straight pipe under laminar conditions. Stable nanofluids are formulated by using the high shear mixing and ultrasonication methods. They are then characterised for their size, surface charge, thermal and rheological properties and tested for their convective heat transfer behaviour. Mathematical modelling is performed to simulate the convective heat transfer of nanoflui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The thermal conductivity and viscosity of the nanofluids was found to be enhanced at higher carbon nanotube concentrations. The forced convective heat transfer of dilute liquid suspensions of nanoparticles (nanofluids) flowing through a straight pipe under laminar conditions was studied by He et al [17]. Their research indicated, using both experiments and mathematical modeling, that nanofluids can substantially enhance convective heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal conductivity and viscosity of the nanofluids was found to be enhanced at higher carbon nanotube concentrations. The forced convective heat transfer of dilute liquid suspensions of nanoparticles (nanofluids) flowing through a straight pipe under laminar conditions was studied by He et al [17]. Their research indicated, using both experiments and mathematical modeling, that nanofluids can substantially enhance convective heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Nanofluids are commonly used in heat transfer units for performance enhancement of cooling fluids. Convective heat transfer using nanofluids, like Al 2 O 3 [ 37 , 38 , 39 ], ZrO 2 [ 39 , 40 ], CNT [ 41 , 42 ], CuO [ 38 ], Cu [ 38 ], and TiO 2 [ 43 , 44 ], have been investigated in numerical studies. Williams et al [ 39 ] investigated the heat transfer and pressure drop in horizontal tubes under turbulent flow conditions by performing experimental analysis on setup using alumina-water (Al 2 O 3 )- and zirconia-water (ZrO 2 )-based nanofluids.…”
Section: Introductionmentioning
confidence: 99%
“…Nowar [14] solved the problem of peristaltic flow of a nanofluid in the regime of Hall current and porous medium. A vast study exploring different aspects of nanofluid may be consulted in the references [15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%